Gwendolyn Brooks : Poetry and the Heroic Voice. - Melhem, D. H. (The University Press of Kentucky, 1987)
Gwendolyn Brooks is one of the major American poets of this century and the first black woman to win the Pulitzer Prize for poetry (1950). Yet far less critical attention has focused on her work than on that of her peers. In this comprehensive biocritical study, Melhem -- herself a poet and critic -- traces the development of Brooks's poetry over four decades, from such early works as A Street in Bronzeville, Annie Allen, and The Bean Eaters, to the more recent In the Mecca, Riot, and To Disembark. In addition to analyzing the poetic devices used, Melhem examines the biographical, historical.